Die kerk vanaf die Ou Testament en die Nuwe Testament tot vandag I: "Voortsetting, vervanging of transformasie?" - Geyser-Fouché, Ananda (HTS teologiese studies, 2017)
In this article the concept of ‘church’ in the Old Testament is investigated, the way this concept started, developed and evolved is discussed, and then the question is asked whether it is possible to employ this concept in our current context. The concepts and terms in the Old Testament which were later translated and developed into the concept ‘church’, are studied first. Secondly the traditional arguments to employ these Old Testament texts to the concept of ‘church’ will be discussed. Finally a study on the nature of Old Testament texts will be conducted as well as the probable authority that it can or may have in other cultures and times in order to examine whether the Old Testament may have something to say about ecclesiology.